2017
DOI: 10.3389/fpls.2017.00746
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Porous Diffusion Modeling of Hydrophilic Ionic Agrochemicals in Astomatous Plant Cuticle Aqueous Pores: A Mechanistic Approach

Abstract: The agricultural industry requires improved efficacy of sprays being applied to crops and weeds in order to reduce their environmental impact and deliver improved financial returns. Enhanced foliar uptake is one means of improving efficacy. The plant leaf cuticle is known to be the main barrier to diffusion of agrochemicals within the leaf. The usefulness of a mathematical model to simulate uptake of agrochemicals in plant cuticles has been noted previously in the literature, as the results of each uptake expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 62 publications
0
32
0
1
Order By: Relevance
“…The process of foliar absorption may take place via the cuticle, stomata, irregularities in the cuticle, trichomes or other epidermal structures ( Fernández et al, 2017 ). In light of cuticular permeability trials, it has been hypothesized that lipophilic molecules should diffuse through the more lipophilic domain of the hydrophobic cuticle ( Niederl et al, 1998 ; Buchholz, 2006 ), while small, polar molecules such as water may follow a different diffusion pathway which is currently not well characterized and has been associated with a “dynamic aqueous continuum” forming due to hydration ( Fernández et al, 2017 ), and to “polar” or “aqueous” pores ( Franke, 1967 ; Schönherr, 2006 ; Tredenick et al, 2017 ) in the cuticle, whose occurrence has never been directly demonstrated so far ( Fernández et al, 2016 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The process of foliar absorption may take place via the cuticle, stomata, irregularities in the cuticle, trichomes or other epidermal structures ( Fernández et al, 2017 ). In light of cuticular permeability trials, it has been hypothesized that lipophilic molecules should diffuse through the more lipophilic domain of the hydrophobic cuticle ( Niederl et al, 1998 ; Buchholz, 2006 ), while small, polar molecules such as water may follow a different diffusion pathway which is currently not well characterized and has been associated with a “dynamic aqueous continuum” forming due to hydration ( Fernández et al, 2017 ), and to “polar” or “aqueous” pores ( Franke, 1967 ; Schönherr, 2006 ; Tredenick et al, 2017 ) in the cuticle, whose occurrence has never been directly demonstrated so far ( Fernández et al, 2016 , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The model takes the form of a nonlinear, quasi-one-dimensional, diffusion model. We will briefly describe the modeling formulation, however we note that a full description can be found in the authors previous work (Tredenick et al, 2017). A schematic diagram of the model domain based on the experimental setup (Kraemer et al, 2009) is shown in Figure 3.…”
Section: Model Frameworkmentioning
confidence: 99%
“…Current mathematical models of penetration of ionic AIs have been created as alternatives to time consuming and expensive field/laboratory studies and fall into two categories: the first employ empirical expressions that require a rate constant to be measured specific to each different plant species, hydrophilic AI, adjuvant and environmental conditions (Forster et al, 2006; Schreiber and Schönherr, 2009, p. 132) and the second incorporate diffusion (Hsu, 1983; Satchivi et al, 2000; Veraverbeke et al, 2003; Mercer, 2007; Pecha et al, 2012). Comprehensive reviews can be found elsewhere (Forster et al, 2004; Trapp, 2004; Tredenick et al, 2017). These models, however, do not include important governing mechanisms such as ion binding, sessile droplet evaporation with water absorption including POD and relative humidity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the major factor influencing uptake in the model was found to be cuticle structure, including tortuosity and density of the aqueous pores. Relative humidity and binding of ions to the surface of cuticles, although still rated high after sensitivity analysis, were less influential [8]. An ion-pairing mechanism has also been proposed as a method to increase the permeability of very polar positively charged cationic drugs through membranes.…”
Section: Introductionmentioning
confidence: 99%